Undergraduate business education students’ perception on information and communication technology use in teaching and learning - Patrick Uzo Osadebe; Joyce Frances Osadebe (International Journal of Evaluation and Research in Education (IJERE), 2020)
The study was carried out to assess the undergraduate Business Education Students’ Perception on the use of Information and communication technology (ICT) in teaching and learning in the University. Thus, to achieve the purpose, two research questions and two hypotheses guided the study. A sample of 100 students was randomly drawn using balloting and proportionate stratified random sampling techniques. A questionnaire of 4-point scale was used to collect data. It has face validity determined through expert judgement, and construct validity verified through factor analysis. The reliability of the instrument was obtained through Cronbach Alpha. A reliability coefficient of 0.82 was obtained as a measure of internal consistency. The data collected were analyzed with mean and Z-test. Mean was used to answer the research questions while Z-test was used to test the hypotheses at the 0.05 level of significance. The result showed that there was high perception of students to use ICT in teaching and learning in the university. There was no significant difference between male and female students as well as 300 level and 400 level students on the use of ICT in teaching and learning. Therefore, it was recommended that ICT should be used in teaching and learning Business Education in the University.